If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 5 = 6 + -1bracket(6x + -5) Reorder the terms: 5 + 3x = 6 + -1bracket(6x + -5) Reorder the terms: 5 + 3x = 6 + -1abcekrt(-5 + 6x) 5 + 3x = 6 + (-5 * -1abcekrt + 6x * -1abcekrt) 5 + 3x = 6 + (5abcekrt + -6abcekrtx) Solving 5 + 3x = 6 + 5abcekrt + -6abcekrtx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6abcekrtx' to each side of the equation. 5 + 6abcekrtx + 3x = 6 + 5abcekrt + -6abcekrtx + 6abcekrtx Combine like terms: -6abcekrtx + 6abcekrtx = 0 5 + 6abcekrtx + 3x = 6 + 5abcekrt + 0 5 + 6abcekrtx + 3x = 6 + 5abcekrt Add '-5' to each side of the equation. 5 + 6abcekrtx + -5 + 3x = 6 + -5 + 5abcekrt Reorder the terms: 5 + -5 + 6abcekrtx + 3x = 6 + -5 + 5abcekrt Combine like terms: 5 + -5 = 0 0 + 6abcekrtx + 3x = 6 + -5 + 5abcekrt 6abcekrtx + 3x = 6 + -5 + 5abcekrt Combine like terms: 6 + -5 = 1 6abcekrtx + 3x = 1 + 5abcekrt Reorder the terms: -1 + -5abcekrt + 6abcekrtx + 3x = 1 + 5abcekrt + -1 + -5abcekrt Reorder the terms: -1 + -5abcekrt + 6abcekrtx + 3x = 1 + -1 + 5abcekrt + -5abcekrt Combine like terms: 1 + -1 = 0 -1 + -5abcekrt + 6abcekrtx + 3x = 0 + 5abcekrt + -5abcekrt -1 + -5abcekrt + 6abcekrtx + 3x = 5abcekrt + -5abcekrt Combine like terms: 5abcekrt + -5abcekrt = 0 -1 + -5abcekrt + 6abcekrtx + 3x = 0 The solution to this equation could not be determined.
| (x-5)(x-1)=280 | | 5x+37=82 | | 4(x+1)+x=-6 | | 25x^2+y^2=25 | | h=80-4t-16t^2 | | -3(x-1)=-6 | | M^2-15m+50=50 | | 4(x+2)+4=36 | | 7-3(4-2x)=0 | | 3-5(2x+9)=8 | | 3/x2-9-7/x-3=-4/x+3 | | y-3y-8/8/35/24+7/3y | | y-8=-2/11(x+12) | | 9t-22=50+t | | (p+12)+(2p-23)+p=669 | | 2a+6a=a | | 1/4-l+3/6+l=0 | | 1-3/7x | | (x+7)/14 | | 6x^3-3x^2+24x+5=0 | | 2x-18=38+9x | | 0=-2x^2+9x+9 | | -b/c+5=d | | -b/3+5=d | | x^2-4.25x+2=0 | | x^2-8.5x+2=0 | | c=100+.8(y-(60+.25y)) | | -1c+6=3c-9 | | 5w+8=3w-6 | | (1/4a)=23 | | 5+16z-4=7z+66-4z | | r^2=14-5r |